On the Need for Legal Regulation of Virtual Currencies - E. V. Voskresenskaya (Сибирское юридическое обозрение, 2018)
The scientific article proves the necessity of legal regulation of relations connected with the use of virtual currencies (crypto-currency). The article examines the constituent elements of the definition of “virtual currency” (crypto-currency) from the position of the object of civil rights. The Author proposes to carry out the legitimation of virtual currency along the way of the object of civil rights and formulates the conclusion that the virtual currency belongs to other property. To construct a definition of a virtual currency, the following constitutive elements should be used: the assignment of a virtual currency to property, the means of payment by an undefined circle of persons, the main functional feature of a virtual currency is the ability to serve as a means of payment on a certain scale, however, this property is not electronic money. Thus, an author's definition of the considered definition of civil law is offered.